2004
DOI: 10.1016/j.ijdevneu.2004.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Gestational treatment with cocaine and fluoxetine alters oxytocin receptor number and binding affinity in lactating rat dams

Abstract: Cocaine administered chronically throughout gestation has been correlated with deficits in maternal behavior, increased maternal aggressive behavior and decreased oxytocin levels in rats. In addition to its effects on oxytocin levels, cocaine is a potent serotonergic, dopaminergic and noradrenergic reuptake inhibitor. Alterations in the dopaminergic and serotonergic systems have been suggested as possibly having a role in cocaine-induced maternal aggression. This study was in part, an attempt to understand som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 64 publications
1
27
1
Order By: Relevance
“…Unfortunately, we found no such studies investigating MA effects on oxytocin levels. However, there are studies (Elliott et al, 2001;Johns et al, 2004;Johns, Lubin, Walker, Meter, & Mason, 1997) showing that acute or chronic cocaine administration alters oxytocin levels and the number and binding affinity of oxytocin receptors in brain areas related to nursing and maternal behavior. Thus, it might be that MA has similar effects on oxytocin as cocaine, because of their similar pharmacokinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we found no such studies investigating MA effects on oxytocin levels. However, there are studies (Elliott et al, 2001;Johns et al, 2004;Johns, Lubin, Walker, Meter, & Mason, 1997) showing that acute or chronic cocaine administration alters oxytocin levels and the number and binding affinity of oxytocin receptors in brain areas related to nursing and maternal behavior. Thus, it might be that MA has similar effects on oxytocin as cocaine, because of their similar pharmacokinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Most findings to date are reported for lactating dams during the earlier postpartum period at more moderate doses of cocaine, with some data available for the later postpartum period at higher doses (Heyser et al 1992). Interestingly, MA alterations following cocaine-treatment in rats are associated with alterations in brain levels of the neuropeptide oxytocin (Johns et al 1997a;Elliott et al 2001), as well as oxytocin receptor binding and affinity in the hypothalamus and limbic system (Johns et al 2004;Jarrett et al 2006). It has been suggested (Johns et al 1994b;Johns et al 1998b;Lubin et al 2003) that cocaine-induced oxytocin system alterations may be at least partially responsible for alterations in MA behavior in cocainetreated rats.…”
Section: Introductionmentioning
confidence: 99%
“…Pedersen et al (1982) demonstrated that oxytocin administration to ovar-iectomized rats can induce and perpetuate maternal behavior, while Lubin et al (2003b) demonstrated that oxytocin antagonist administration into the central amygdala increases maternal aggression. Johns et al (2004) found that gestational treatment with fluoxetine (a serotonin reuptake inhibitor) resulted in a reduction in oxytocin receptor affinity and an upregulation of oxytocin receptor number in the amygdala. Several brain regions are suggested as being relevant to maternal behavior and/or aggression in the rat, including the medial preoptic area (MPOA), ventral tegmental area (VTA), hippocampus, and amygdala, and reductions in oxytocin in these areas correlate with deficits in maternal behavior and/or aggression (Ferris et al, 1992;Gaffori and Le Moal, 1979;Johns et al, 1995Johns et al, , 1997Kimble et al, 1967;Lubin et al, 2003b;Numan and Smith, 1984;Numan, 1994a,b).…”
Section: Introductionmentioning
confidence: 99%